Surrogatarrangemang i ett rättighetsperspektiv - vem har rätt till vad och vem har rätt till vem? - Rosberg Gustafsson,Cecilia (2011)
Is everyone entitled to a right to parenthood? People may have a sense of what should be potential common rights even in cases where the government cannot always be considered liable to offer help, as in supporting those suffering from infertility. As a supplementary question one can ask: into what considerations could the right to parenthood extend? When it comes to surrogate motherhood, amounts are usually the subject of some sort. Money is not always the primary concern, the amount of risk that subjects involved in the surrogacy arrangement are exposed to are also often unclear. In a world where surrogate motherhood is increasingly becoming an accepted method against infertility, Swedish legislation currently considers this method illegal, and it is from there that legal complications arise. The fact that this method is against the law does not, however, automatically denote that the subject will never be debated in court or before governmental institutions. For example, although a Swedish citizen cannot employ a surrogate mother to carry a child in Sweden, options might still be available abroad. Then, when the child is born and brought back with its intended parents, problems with registering the child and the proposed guardians might arise. Difficult disputes could also occur within the nature of family law, with issues such as concerning inheritance law or maintenance claims. The aim of this essay is to initially present the subject of surrogacy from a legal rights perspective. Furthermore, I will illustrate discussions on the subject in Swedish law and analyze this in relation to the chosen focus, with help of certain international practical examples. Whilst focusing on rights, provisions from the European Convention for the Protection of Human Rights and Fundamental Freedoms, as well as from the UN Convention on the Rights of the Child, are relevant to introduce. When trying to define surrogacy one finds that many ethical aspects arise. In order to construct a considered opinion on the matter these issues need to be deconstructed and evaluated. One important consideration is whether different motives of the parties involved in an arrangement should be accepted or not. Another important question, which the debate should address, is how an agreement on surrogacy should be assessed from a contract law perspective. Are there circumstances, depending on the nature of surrogacy, which should make contracts void no matter the wording? This debate contains reasoning regarding human values and, in cases where these values are ignored, the risk of exploitation. Swedish law contains legislation on reproductive technology but it does not allow surrogacy. Mater simper certa est, meaning that the mother of a child is always certain, has been given fundamental value in Swedish family law and signifies the basis of the negative attitude against surrogate motherhood. The principle was also given assured significance in a case set before the Swedish Supreme Court when it was debated how to merge different aspects of parenthood; genetic, social and legal, when those address different persons. The Swedish legal situation aside, there are other countries where surrogacy arrangements are legally offered as package deals. Different legislations lead to different growths and effects on the surrogacy market and it should be valuable to consider these differences when deciding what legislation one finds desirable for their own society.
Keywords: surrogat; surrogatmoder; surrogatmödraskap; moderskap; EKMR; barnkonventionen; barnets bästa; assisterad befruktning; surrogacy; surrogate